Novel pre-treatment for lignocellulosic biomass delignification using alkaline-assisted ohmic heating - Ab Aziz, Izzah Farhana; Che Man, Hasfalina; Hamzah, Muhammad Hazwan; Jamali, Nur Syakina; Omar, Rozita (Universiti Putra Malaysia Press, 2023)
Lignocellulosic biomass (LCB) is a common substrate for biogas and bioethanol production due to its significant properties and abundance. However, it has a unique recalcitrant structure that can inhibit the production of biogas, which necessitates pre-treatment of the substrate to obtain higher cellulose or sugars ready for microbial hydrolysis in producing biogas. In this study, a novel approach for empty fruit bunch (EFB) pre-treatment has been made: ohmic heating pre-treatment. This method is conventionally used in the food industry for pasteurization and extraction. It involves electric current and resistance inside the material that releases heat (Joule effect). A preliminary study has been done to figure out the potential of alkaline assisted with ohmic heating (AA-OH) pre-treatment for EFB. Lignin reduction for AA-OH EFB is higher than EFB that undergoes only size reduction (SR) pre-treatment, which are 15.54% and 11.51%, respectively. After confirming the potential of ohmic heating as one of the pre-treatment methods for EFB, three parameters were investigated (reaction time, temperature, and solvent concentration) by one factor at a time (OFAT) testing to obtain the optimum condition for AA-OH pre-treatment. The optimal condition for achieving a high reduction in lignin (86.9%) and hemicellulose (75%) while also showing a significant increase in cellulose (63.2%), which is desirable for the fermentation process, is achieved by using 4% w/v of NaOH, ohmic-heated at a temperature of 120°C for 25 minutes. To sum up, this developed ohmic heating pre-treatment technique can be applied to LCB prior to biogas or bioethanol production.